(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the role of Orthodox Church in the marriage contracting in Ukraine in the 18-th century. A big influence both of canon and customary law in a such conservative sphere of social life as Family and Marriage is pointed out. The process of interference of the state in the church jurisdiction is also analyzed. This process led to the reduction of church’s power and influence.